Artificial Intelligence for English Learning Enhancing Vocabulary Acquisition - Mónica Herazo Chamorro, Carlos Gómez Díaz, Mercedes del Carmen Rodríguez Altamiranda, Nini Johana Villamizar Parada, Ligia Rosa Martinez Bula, Marisela Restrepo Ruiz (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The acquisition of vocabulary is a fundamental aspect of language learning, particularly in English, which serves as a lingua franca in global communication. Traditional methods of vocabulary acquisition often rely on rote memorization and repetition, which can be tedious and ineffective for many learners. With the advancements in artificial intelligence (AI) technologies, there exists an opportunity to revolutionize vocabulary acquisition through innovative and personalized approaches. This paper explores the potential of AI in enhancing vocabulary acquisition for English learners. It begins by examining the shortcomings of traditional methods and the challenges faced by learners in vocabulary acquisition. Subsequently, it delves into the various ways in which AI can be leveraged to address these challenges effectively. One of the primary advantages of AI in vocabulary acquisition is its ability to provide personalized learning experiences tailored to individual learners’ needs and preferences. Through adaptive algorithms and machine learning techniques, AI platforms can analyze learners’ strengths, weaknesses, and learning styles to deliver customized vocabulary exercises and content. This personalized approach not only increases engagement but also maximizes retention and understanding.